2021
DOI: 10.3390/ijerph182413136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of WW Domain-Containing Oxidoreductase Gene Polymorphism on Clinicopathological Characteristics of Patients with EGFR Mutant Lung Adenocarcinoma in Taiwan

Abstract: Lung adenocarcinoma is the most common histological type of non-small cell lung cancer, which accounts for the majority of lung cancers. Previous studies have showed that dysregulation of WW domain-containing oxidoreductase (WWOX) participates in the generation of several cancer types, including lung cancer. However, whether these WWOX polymorphisms are related to the clinical risk of epidermal growth factor receptor (EGFR)-mutated lung adenocarcinoma is worthy of investigation. The present study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Several studies have consistently revealed prominent associations between the polymorphisms of WWOX and the aggressive, poor prognosis of various malignancies, such as urothelial, esophageal squamous cell, hepatocellular, lung, pancreatic, and thyroid cancers 30 , 31 , 36 - 41 . To the best of our knowledge, the present study is the first to investigate the association between the polymorphisms of WWOX and the clinicopathologic features of resectable PCa in Taiwanese men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have consistently revealed prominent associations between the polymorphisms of WWOX and the aggressive, poor prognosis of various malignancies, such as urothelial, esophageal squamous cell, hepatocellular, lung, pancreatic, and thyroid cancers 30 , 31 , 36 - 41 . To the best of our knowledge, the present study is the first to investigate the association between the polymorphisms of WWOX and the clinicopathologic features of resectable PCa in Taiwanese men.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic polymorphisms have been associated with PSA level, tumor susceptibility, tumor grade, and mortality in PCa [21][22][23][24][25][26][27]. Moreover, WWOX SNPs have been reported in numerous cancers [28][29][30][31][32]. However, the association between the polymorphism of WWOX and the risk of the postoperative BCR of PCa remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor ( EGFR ) mutations in the tyrosine kinase domain are common in NSCLC patients, with higher rates particularly in those with adenocarcinoma, non-smokers, females, and Asian populations [ 5 , 6 ]. Around two-thirds (67.1%) of patients with EGFR -mutant NSCLC have classical EGFR mutations (exon 21 L858R point mutation or exon 19 deletions [Ex19del]) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the important role of EGFR mutation status in NSCLC development, we decided to explore interactions amongst crucial genes and EGFR status in NSCLC and LUAD. Interleukin-17A, the tumor suppressor protein WW domain-containing oxidoreductase, tissue inhibitor of metalloproteinase 3 (TIMP3), and long noncoding RNA H19 polymorphisms have all been associated with clinicopathologic characteristics in lung cancers [ 5 , 9 , 12 , 13 ]. These four studies have helped to identify subgroups of patients at high risk for LUAD progression.…”
Section: Introductionmentioning
confidence: 99%